Reflections on social suffering and chronic kidney disease - Juliana Graciela Vestena Zillmer; Denise Maria Guerreiro Vieira da Silva (Universidade Federal de Santa Maria, 2016)
Aim: theoretically discuss the concepts of social suffering of people with chronic conditions. Methods: this is a theoretical reflection based on texts about social suffering and a statement of a person with chronic kidney disease. The analysis consisted of the repeated reading of such narrative and immersion in the data to articulate theoretical aspects of social suffering. Results: three reflective categories were developed. The first one is a brief contextualization about social suffering; the second is the narrative of a person with kidney disease which was used as a broader context for the third stage of the reflection, in which engaged along considerations and framework interfaces with the narrative. Conclusion: The social suffering referente may contribute to broaden the traditional way of looking at a person's suffering with chronic conditions; as well as raise awareness and guide the disciplines that constitute the health care, both at the micro level, in the fulfillment of care, as at the macro, with public policy development